THE APPLICATION OF CROSSWORD PUZZLES IN MATHEMATICS LEARNING - Yasinta Yenita Dhiki; Kornelia Bunga; Maria Icha Florensia Seku; Alexcia Kristina Ja’a; Yohanes Pedo One; Ardianus Beda Keda Kurman; Aleksandrianus Au (LPPM Universitas Flores, 2026)
Mathematics learning often causes difficulties for junior high school students, especially in basic topics such as integer operations. Many students encounter difficulties understanding the concepts of addition, subtraction, multiplication, and division of integers, particularly when the material is presented as word problems. To overcome these problems, we, students of the Mathematics Study Program at Universitas Flores, implemented an innovative learning medium in the form of crossword puzzles integrated with Student Worksheets (Lembar Kerja Peserta Didik/LKPD). This activity was conducted at SMPK Wawonato and involved 20 students of class VII B. The crossword puzzles were designed to contain word problems related to integer operations, while the student worksheets functioned to review students’ initial and final abilities. The results of the activity showed that implementing crossword puzzles and student worksheets increased students’ enthusiasm and motivation for learning and improved their understanding of integer operations. Students became more actively involved in group discussions and were able to solve word problems more effectively.